algebra

How do I solve this equation?
a/5 - 1/5 = -2

multiply both sides by 5.
then add one to each side.

  1. 👍
  2. 👎
  3. 👁

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math

    A student is trying to solve the set of two equations given below: Equation A: x + z = 6 Equation B: 2x + 4z = 1 Which of the following is a possible step used in eliminating the z-term? Multiply equation B by 4. Multiply equation

  2. algebra

    assume x > 0. what percent of 8x is 5x? i know that the equation is 5x/8x = p/100 and i have to multiply both sides by 100, but i'm not sure how to multiply 100 * 5x / 8x? what is 65% of 80x? again, i know that the equation is

  3. simultaneous equations

    Solve 2a + b = 3 4a - 5b = 20 My attempt Multiply the first equation by 5 So, 10a + 5b = 15 4a - 5b = 20 Add them together 14a = 35 Divide both sides by 14 a = 2.5 Substitute (I have done it with the second one) 10 - 5b = 20 Take

  4. math

    A=1/2h (b1 + b2) Solve for b1 A=1/2h (b1 + b2) Solve for b1 I assume this is A = (1/2)(h)(b1 + b2); i.e., the h is in the numerator and not the denominator Multiply both sides by 2. 2A = (2*1/2)h(b1 + b2). 2*1/2 on the right side

  1. algebra

    Which could be a first step in solving the equation 1/4x+1/2=3/4x in an efficient way? Select two answers. A.multiply by 4 on both sides B.multiply by 2x on both sides C.subtract 1/4x from both sides D.add 1/2 to both sides plz

  2. Mathematics (8th grade)

    Quinda begins to solve the equation Negative 4.5 x + 3 = 2 minus 8.5 x by adding 8.5x to each side of the equation. Which next step would result in the variable terms and constant terms being on different sides of the equals sign?

  3. Algebra

    The first step to solve for y in y/3= 6 + x is A) to subtract x from both sides of the equation. B) to subtract y/3 from both sides of the equation. C) to divide each term on both sides of the equation by 3. ******* D) to multiply

  4. Pre Cal.--Check my work?

    Solve the system of equations: x - y - z = 2; x + 2y - 2z = 3; 3x - 2y - 4z = 5? well, you have: 1- x-y-z=2 2- x+2y-2z=3 3- 3x-2y-4z=5 multiply both sides of the equation 1 by 2: x-y-z=2 ===> 2x-2y-2z=4 add this by equation 2:

  1. algebra II

    Select the best possible first step to solving the system by first eliminating the y variable. x + 8y = –4 2x – 4y = –13 Multiply the first equation by 2. Multiply the second equation by 2. Multiply the first equation by

  2. PLEASE HELP ME!!!

    What is the first step in solving the problem, 3x-8/12=9? A) Add 8 to both sides. B) Multiply by 12 on both sides. C) Divide by 3 on both sides. D) Subtract 9 on both sides.

  3. Algebra

    Solve S=a/(1-r) for r S = a/(1-r) Multiply both sides by 1-r S*(1-r) = [(1-r)*a]/(1-r) Simplify S*(1-r) = a Multiply terms on the left. S - S*r = a Subtract S from both sides. S-S*r - S = a - S Simplify -S*r = a - S Multiply both

  4. algebra2

    solve the systems of equation: First : 4x-2y = 2 Second: y = -4x-7 Should i solve by using substitution, elimination or multiply then use elimination? Try adding them. Add up the left sides and the right sides (after rearranging

You can view more similar questions or ask a new question.